ANALISIS PEMBENTUKAN DANANTARA DALAM UPAYA PENCEGAHAN MANIPULASI HARGA EKSPOR KOMODITAS DI INDONESIA: STUDI KASUS PADA INDUSTRI CPO INDONESIA TAHUN 2026 - Andini Rahayu Putri; Dimas Saragih; Febry Tarigan; Rizqi Alhaq Nasution; Yanri Girsang; Putri Kemala Dewi (STKIP Subang, 2026)
Indonesia is one of the largest commodity-producing countries in the world, particularly in the Crude Palm Oil (CPO) sector, which contributes significantly to national economic growth and foreign exchange earnings. However, the high volume of CPO exports has also created various problems in international trade governance, especially related to export price manipulation practices such as under invoicing and transfer pricing. These practices potentially reduce state revenue from taxes and export duties. This study aims to analyze the establishment of Danantara as a government strategy to prevent export price manipulation in Indonesia’s CPO industry in 2026. The research uses a qualitative descriptive method with a literature study approach by collecting secondary data from books, journals, government reports, and relevant scientific articles. The results of the study indicate that the establishment of Danantara represents the government’s effort to strengthen supervision of export commodity trade through increasing transparency, improving coordination among institutions, and monitoring international trade transactions more effectively. The study also finds that stronger supervision is needed to minimize transfer pricing practices and improve state revenue from the export sector. Therefore, Danantara is expected to become an important instrument in improving the governance of commodity exports in Indonesia in a more transparent, accountable, and efficient manner.